Residue retention and nitrogen management of preceding crops influences the productivity, profitability and environmental footprints of summer mungbean in maize-based cropping systems under conservation agriculture. Issue 11 (19th September 2023) - Kadam, Praveen V.; Jat, Shankar Lal; Mahala, Deep Mohan; Parihar, C. M.; Singh, A. K.; Kumar, Bhupender; Gambhir, Geetika; , Radheshyam; Chandra, M. Sharath
ABSTRACT: A field study was carried out during 7th and 8th cycles in conservation agriculture to assess the influence of cropping system {(maize-mustard (MMu) and maize-wheat (MW)}, residue application {(with residue (WR) and without residue (WoR)} and precision nitrogen management options in preceding crop {recommended dose of N (RDN), 33%, 50% and 70% basal RDN + green seeker (GS) based N application} on succeeding summer mungbean. The WR enhanced 17.5% and 13.6% seed yield with 29.1% and 12.06% higher net returns of mungbean in MMu and MW, respectively. Residue mulching with 50+ GS significantly increased the seed protein content. The MMu with WR and 33+ GS produced higher environmental footprints (532.8 and 479.5 kg CO2 -e Mg −1 ), respectively. Similarly, significantly higher gross energy was produced in WR (44.2 × 10 3 MJ ha −1 ) while, WoR produced higher net energy (11.7 × 10 3 MJ ha −1 ) under MMu compared to MW (43.1 and 8.31 MJ ha −1 ), respectively. Thus, growing of mungbean under maize-based cropping systems with residue and 50+ GS guided N fertilization to previous crops (maize-wheat/mustard) improved yield and net returns with lower environmentally footprints and energy consumption in Indo-Gangetic plains (IGP) and similar agro-ecologies.